PERSEPSI MASYARAKAT TERHADAP KONSERVASI HUTAN MANGROVE DAN BENCANA DI DESA LEUGE KABUPATEN ACEH TIMUR - M. Fajrianda; Yusya Abu Bakar; Syamsidik . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
One of the source of flooding in coastal area is the felling of mangrove trees and also land conversion from mangrove forest to settlement.  Therefore, mangrove conservation is conducted as an efforts to reduce impact of disaster. The goal of this research is to know the community perception of Luege village about forest conservation and hazards before and after Tsunami earthquake 2004; to know about the influencing factor  of  community’s perception differentiation  in Leuge Village to mangrove forest conservation; and also dominant factor that influence community perception in mangrove forest conservation. This research is kind of descriptive with qualitative approach. The subject of this research is Leuge Village’s community where the date of this research was gained by observation and interview. The result of this research resumed that Leuge Village’s Community had already owned the awareness that the mangrove forest conservation have the  linked or relationship with the hazards that frequently happened annually. This is due to community in place directly face the negative effects as the result of environment degradation. Perception are influence from ecology, economy, social, culture, and leadership factors. The economy factor is the main factor that very dominant influencing the change of community perception[Z1]  [Z1]Abstrak maksimal 200 kata